Field measurements of Tropical Storm Aere (1619) via airborne GPS‐dropsondes over the South China Sea. (18th October 2020) - Fu, J. Y.; Shu, Z. R.; Li, Q. S.; Chan, P. W.; Hon, K. K.; He, Y. C.
Abstract: In the past two decades, Global Positioning System (GPS)‐dropsonde has been developed as an effective tool to explore the internal structures of tropical cyclones (TCs). To facilitate the short‐term forecasting of the TCs' intensity and track over the Hong Kong Flight Information Region (HKFIR), Hong Kong Observatory (HKO) launched in 2016 reconnaissance campaigns by using airborne GPS‐dropsondes. On October 7, 2016, when Tropical Storm Aere (1619) got close to Hong Kong, 10 dropsondes were released from a reconnaissance aircraft at 10 km altitude to sample the TC at different storm‐relative positions. This offers a valuable opportunity to examine the functional performance of the dropsonde system. In the study, the validity of dropsonde measurements is first examined, mainly by comparing the results with those collected contemporaneously by radiosonde balloons from a nearby station. Observational results of the structural characteristics are then discussed. Evidence was observed for the invasion of the storm's inner structure by background atmosphere, which was unfavourable for the intensification of Aere in the following time. Meanwhile, a height‐resolving model of the TC's pressure field is proposed. It is also observed that the parachutes of two dropsondes failed to deploy during the descending period. The results presented here are expected to provide useful information for a better understanding of the in‐situ measurements from dropsondes deployed over the HKFIR, and for advancing the knowledge on TC's inner structure. Abstract : The overall credibility and accuracy of the dropsonde measurements were examined. It was also found that the parachutes of two dropsondes failed to deploy during the descending period. The ensemble‐mean profile of air pressure followed the barometric formula. The profiles of the tropical cyclone pressure deficit were linear with barometric altitude, with the slope increasing linearly with the increase of the pressure deficit at mean sea level. Evidence was observed for the invasion of the storm's inner structure by the background atmosphere, which was unfavourable for the intensification of Aere in the following time.